PENILAIAN KINERJA DENGAN MENGGUNAKAN METODE BALANCED SCORECARD - Widyastuti, Khamidah Nur; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze the implementation of Balanced Scorecard on Pawiyatan Junior High School Surabaya. Descriptive analysis which is done by using qualitative approach is used as the data analysis technique since this research does not use elements of figures but it is done by presenting descriptions and explanation. Based on the data analysis, the conclusion can be gained by using Balanced Scorecard approach from its four perspective, i.e.: the financial perspective shows that the budget which has been accepted from School Operation Assistance (BOS), BOPDA, investment fund / committee fee (SPP) with the realization of fund on Pawiyatan Junior High School Surabaya. On the customer perspective, the indicator is Number of New Customer, Number of Complain can be said well enough, since the Pawiyatan Junior High School Surabaya has run the curriculum standard and the standard of teaching â learning process properly. Meanwhile, the growth and learning perspective shows that the performance of Pawiyatan Junior High School Surabaya is well, it has been shown by the numbers of education and training which have been done by the school and the satisfaction level of the employees. It is recommended that in the future the Pawiyatan Junior High School Surabaya had better use the Balanced Scorecard in assessing the performance of the employees. Moreover, the Pawiyatan Junior High School Surabaya had better use the learning system through the internet based of Information Communication and Technology (ICT).Keywords: Performance, The Implementation of Balanced Scorecard, School Based.